Hematological and Biochemical Abnormalities Associated with Mortality Among Hospitalized COVID-19 Patients: A Retrospective Single Center-Based Study. - Muhamed, Aisha Ali; Salema Qowaider; Makarim Osman; Sara Abdulla (Khalij-Libya Journal of Dental and Medical Research, 2023)
Background and objectives: Severe acute respiratory coronavirus 2 (SARS-CoV-2) has emerged as a major public health threat. Characteristics of patient laboratory test results have important implications for predicting disease prognosis, especially in countries with limited health resources. This is a retrospective, cross-sectional, single-center study of 402 COVID-19 patients. Methods: Hematology parameters, coagulation parameters, liver function test (LFT) and renal function test (RFT) results were collected and compared between survivors and non-survivors to identify predictive biomarkers of death. Collected data were statistically analyzed using SPSS V.26. Results: 114 patients died with a mean age of 75.8±16.3 years old which was significantly high compared to the survivors' group. (p=0.00). There was no significant difference in hemoglobin level (Hb) and blood cells count between the two cohort (all P > 0.05). non survivors group significantly has higher level of lactate dehydrogenase (LDH) than the survivors’ group (P < 0.05). LFT & RFT results show no significant difference between the survivors and non-survivors’ cohort (P > 0.05). Erythrocyte Sedimentation Rate (ESR) and serum C reactive protein (CRP) were high. However, the difference between the survivors and death cohort was not statistically significant (P > 0.05). D-dimer level was significantly higher among non-survivor group compared to survivors (P< 0.05). Conclusion: we conclude that some demographic features and laboratory investigation could be used to identify high risk patients especially in low resources hospitals.